2014
DOI: 10.1007/s11427-014-4733-z
|View full text |Cite
|
Sign up to set email alerts
|

No correlation between the diversity and productivity of assemblages: evidence from the phytophage and predator assemblages in various cotton agroecosystems

Abstract: Biodiversity research has shown that primary productivity increases with plant species number, especially in many experimental grassland systems. Here, we assessed the correlation between productivity and diversity of phytophages and natural enemy assemblages associated with planting date and intercropping in four cotton agroecosystems. Twenty-one pairs of data were used to determine Pearson correlations between species richness, total number of individuals, diversity indices and productivity for each assembla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The relationship between species richness and productivity has been a central but controversial issue in plant ecology for a decade. A growing number studies have documented the productivity–richness relationship (Bai, Han, Wu, Chen, & Li, ; Gao, Men, & Ge, ), mostly finding that a unimodal relationship at scales from local to landscape, although several studies have found no correlation between species richness and productivity (Fraser et al, ; Gao et al, ). Here, we found a positive relationship between species richness and AGB across both community and all the plant functional groups except for sedges (Figures and ).This is promoted to some degree by the greater gains in soil resources in more diverse plant communities (Fornara & Tilman, ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between species richness and productivity has been a central but controversial issue in plant ecology for a decade. A growing number studies have documented the productivity–richness relationship (Bai, Han, Wu, Chen, & Li, ; Gao, Men, & Ge, ), mostly finding that a unimodal relationship at scales from local to landscape, although several studies have found no correlation between species richness and productivity (Fraser et al, ; Gao et al, ). Here, we found a positive relationship between species richness and AGB across both community and all the plant functional groups except for sedges (Figures and ).This is promoted to some degree by the greater gains in soil resources in more diverse plant communities (Fornara & Tilman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no consensus has been obtained regarding the relationship between productivity and species richness along natural gradients (Tredennick et al, ). Three dominant views were put forth regarding the productivity–richness relationship in terrestrial ecosystems, that is, hump‐shaped or U shaped (Ni, Wang, Bai, & Li, ; Waide et al, ), positive relationship (Bai et al, ; Marquard et al, ), and no correlation (Gao, Men, & Ge, ). The hump‐shape indicated that plant diversity reach its highest value at intermediate levels of productivity owing to density limitation (Oksanen, ), dispersal limitation, and evolutionary history (Zobel & Pärtel, ).…”
Section: Introductionmentioning
confidence: 99%